The Dengue Virus NS5 Protein Intrudes in the Cellular Spliceosome and Modulates Splicing - de Maio, Federico Andres (2016)
Dengue virus NS5 protein plays multiple functions in the cytoplasm of infected cells, enabling viral RNA replication and counteracting host antiviral responses. Here, we demonstrate a novel function of NS5 in the nucleus where it interferes with cellular splicing. Using global proteomic analysis of infected cells together with functional studies, we found that NS5 binds spliceosome complexes and modulates endogenous splicing as well as minigene-derived alternative splicing patterns. In particular, we show that NS5 alone, or in the context of viral infection, interacts with core components of the U5 snRNP particle, CD2BP2 and DDX23, alters the inclusion/exclusion ratio of alternative splicing events, and changes mRNA isoform abundance of known antiviral factors. Interestingly, a genome wide transcriptome analysis, using recently developed bioinformatics tools, revealed an increase of intron retention upon dengue virus infection, and viral replication was improved by silencing specific U5 components. Different mechanistic studies indicate that binding of NS5 to the spliceosome reduces the efficiency of pre-mRNA processing, independently of NS5 enzymatic activities. We propose that NS5 binding to U5 snRNP proteins hijacks the splicing machinery resulting in a less restrictive environment for viral replication.